Pencegahan Paham Radikal di Kalangan Siswa pada Sekolah Menengah Atas Negeri di Kalimantan Timur - Mahmuji Mahmuji (FENOMENA, 2021)
Radical understanding is a common phenomenon that can occur in a society with diverse motives, both social and political, cultural and religious, which is marked by acts of extreme, and anarchist as a form of rejection of the symptoms faced. In this case, everyone has the potential to become radical and radical, depending on whether the environment (habitus) supports it or not. This research use descriptive qualitative approach. Sources of data using purposive sampling. The results showed that the implementation of radical prevention programs at State Senior High School in Samarinda city, namely (1) Academic program in the form of religious and multicultural coaching conducted during the lesson. (2) Non-academic program that is extracurricular activities that run outside of lesson. Various factors that influence the learning process come from supporting and inhibiting factors such as the supporting factors are: Vision and mission of the school, community interest, conducive school atmosphere, facilities and infrastructure. While the inhibiting factors are: The use of information and communication technology, and mass media. Implementation of the implementation of the program is the formation of a moderate pattern of understanding among students so that none of it shows the existence of practical abnormalities of rites and thoughts.